Respuesta del cultivo de lechuga crespa (lactuca sativa) a la aplicación de tres láminas de riego deficitario en el cantón Latacunga, provincia de Cotopaxi campus Salache, 2022 - Moreno Moreno, Steeven Bladimir (2022)
In semi-arid areas, water consumption is affected by the inappropriate use of agriculture, in this situation, it is important to evaluate the response of the curly lettuce crop (Lactuca sativa) to the application of three sheets of deficit irrigation. The agronomic behavior of the crop was carried out under three irrigation layers at 100% crop evapotranspiration (ETc), 80% ETc, 60% ETc, using a completely randomized design and Tukey test at 0.05%. An economic evaluation was also carried out using cost-benefit indicators for each treatment, considering a 20% reduction to estimate the farmer's real yield. The results allowed us to identify that all the variables showed highly significant differences between the three treatments, that is, the plant is influenced by the application of the irrigation sheets. A reduction of the sheets of 20 and 40% affects the crop yield by 0.4 and 0.29 kg respectively. For the profitability of the crops, it can be verified that it is profitable to implement a drip irrigation system in T1 (100% ETc) and T2 (80% ETc), since there is no profitability in T3 (60% ETc), As a conclusion of this investigation, at the time of giving irrigation it is determined based on (Kc) that the sheet T1 (100% ETc) , is the most suitable for better production and profitability. The use of high-frequency drip irrigation is a sustainable measure to optimize irrigation management in situations of water scarcity.